Seroprevalence of and risk factors for Leishmania seropositivity in a sample population of Western Sicily (Italy) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Leishmania is a vector-borne parasite responsible for significant morbidity and mortality worldwide. The aim of this study was to assess the prevalence of and risk factors for Leishmania infantum seropositivity in a sample of Sicilian population.Methods: A total of 260 subjects were interviewed using a standardized questionnaire and requested for an venous blood sample.Results: Overall, 36 subjects (13.8%) were seropositive against L. infantum with a statistically significant higher prevalence of positivity in older subjects (p=0.04). After adjustment for age, a higher risk for Leishmania seropositivity was found in subjects who had pets living outdoors and untreated with anti-pests, and in those who were current smokers (adj-OR = 2.95 and adj-OR = 3.11, respectively; p < 0.05).Conclusions: Our data confirm that Leishmania infections among Sicilian citizens can be considered relatively frequent, suggesting that a percentage of Leishmania seropositivity can be probably attributed to exposure to both old and new risk factors.